2013
DOI: 10.7748/ns2013.03.27.28.35.s9612
|View full text |Cite
|
Sign up to set email alerts
|

The role of technology and digital gaming in nurse education

Abstract: There is growing evidence that using e-learning and digital gaming technology can support students in their learning. An international project, Continuing/Higher Education in Research Methods Using Games, funded by the European Commission's Lifelong Learning Programme and led by a team at the University of the West of Scotland, aims to develop interactive activities and games to support nursing and social science students. This article looks at the scope of the project in helping to deliver nurse education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 0 publications
1
10
0
1
Order By: Relevance
“…In addition, the change was sustained 3 months after the intervention. These results are consistent with a growing body of literature supporting gaming theory as an educational tool (Elzein, Drenkard, Deyo, & Swartwout, 2015;Johnston et al, 2013). Because there was a statistically significant difference in adherence to ETCO2 protocol following completion of the game, it can be inferred that clinicians were more mo-tivated to adhere to the ETCO2 protocol after playing the game.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, the change was sustained 3 months after the intervention. These results are consistent with a growing body of literature supporting gaming theory as an educational tool (Elzein, Drenkard, Deyo, & Swartwout, 2015;Johnston et al, 2013). Because there was a statistically significant difference in adherence to ETCO2 protocol following completion of the game, it can be inferred that clinicians were more mo-tivated to adhere to the ETCO2 protocol after playing the game.…”
Section: Discussionsupporting
confidence: 87%
“…Clinical education is ongoing, and new techniques are needed to keep clinicians up to date on new evidencebased practices (Johnston, Boyle, MacArthur, & Manion, 2013). Traditionally, students and HCPs receive much of their formal education in a lecture hall setting in conjunction with assigned reading material.…”
Section: Knowledge and Comfort Of Monitoringmentioning
confidence: 99%
“…[7][8][9] These games are widely applied within the educational field to facilitate students' learning through the integration of information in a competitive active environment. 10,11 An educational game is defined as an instructional method that requires the learner to participate in a competitive activity with preset rules.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that the COPD game for outpatient care could be an accessorial content and teaching strategy. The use of this emerging technology is not seen as a replacement for traditional teaching approaches, but as complementing and enhancing the student experience [5].…”
Section: Suggestionsmentioning
confidence: 99%
“…Johnston et al [5] defined serious gaming as software applications where learners can immerse themselves in virtual environment activities that allow them to tackle problems relevant to their discipline and proposed that digital games could support the strategies for nursing education. Their team implemented digital games to teach research methods and statistics for students in nursing and social science.…”
Section: Introductionmentioning
confidence: 99%